A method for preparing konjac composite xerogel with rapid swelling property
By gently cross-linking the synergistic effect of sodium carboxymethylcellulose and konjac glucomanan, combining cyclodextrin and sodium bicarbonate to form a porous structure, the problem of excessive cross-linking during konjac glucomanan cross-linking is solved. A konjac composite xyrogel with high swelling rate and long-term satiety is achieved.
Patent Information
- Application Number
- CN202211597900.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-12-12
AI Technical Summary
Konjac glucomanan is prone to excessive cross-linking during cross-linking, resulting in a decrease in water absorption rate and is unable to effectively provide a long-term feeling of fullness.
By gently crosslinking the synergistic effect of sodium carboxymethylcellulose and konjac glucomannan, combining cyclodextrin and sodium bicarbonate to form a porous structure, optimizing hydrogen bond interaction and adhesion effect, and improving swelling rate and satiety time.
It achieves high swelling rate, rapid swelling and long-term satiety, avoids the decrease in water absorption caused by excessive cross-linking, and is suitable for long-term consumption and is healthy and safe.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of konjac xerogel, in particular to a method for preparing a konjac composite xerogel with rapid swelling performance. Background Art
[0002] People of all ages in today's society need to pay great attention to weight control. Weight control is one of the important means for people of all ages to manage their own bodies. It is also an important part of obesity treatment and plays a pivotal role in the field of life and health. The core of weight control is to control calorie intake, that is, the daily calorie intake is equal to or less than the calories required for one's own basal metabolism. The most direct way is to maintain a balance of calorie income and expenditure by controlling diet.
[0003] Konjac glucomannan is an alkaline food derived from natural products. It has the characteristics of low calories, low fat and high fiber, and is an ideal dietary fiber. Konjac glucomannan has a high water absorption rate, and can produce a significant sense of fullness after taking a certain amount. However, the swelling rate of Konjac glucomannan is slow, and it does not have a specific shape when dispersed in water to become a fluid with fluidity. Therefore, it can be quickly discharged from the stomach to the intestine after consumption, and the duration of fullness is not long enough. Therefore, the modification of Konjac glucomannan by physical compounding and chemical cross-linking can effectively improve the above two problems.
[0004] Sodium carboxymethyl cellulose is a widely used food additive with the characteristics of no calories, fast swelling, strong adhesion, etc. However, sodium carboxymethyl cellulose is easily soluble in water before cross-linking. The sodium carboxymethyl cellulose obtained after cross-linking is insoluble in water by using polyacid and sodium carboxymethyl cellulose for dehydration esterification reaction and cross-linking, but the swelling rate is maintained, so it can be used as an auxiliary agent for konjac. The two can be effectively cross-linked and obtain good water absorption and swelling effects. However, if the conditions are not properly controlled, it will lead to excessive cross-linking, which will significantly reduce the water absorption rate of konjac glucomannan. Summary of the invention
[0005] In order to solve the technical problems of excessive cross-linking and obvious decrease in water absorption rate of konjac glucomannan in the cross-linking process of konjac gel, the present invention provides a preparation method of konjac composite xerogel with rapid swelling property, which can effectively achieve high swelling rate and rapid swelling of the product through obvious synergistic effect between slightly cross-linked sodium carboxymethyl cellulose and slightly cross-linked konjac glucomannan, and the cross-linked carboxymethyl cellulose can adhere to konjac into large blocks after absorbing water, and can also effectively provide satiety and prolong satiety time.
[0006] The specific technical scheme of the present invention is: the present invention provides a method for preparing a fast-swelling konjac composite xerogel, comprising the following steps:
[0007] S1, preparation of slightly cross-linked konjac xerogel;
[0008] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose xerogel: adding glyceryl monostearate to ethanol and heating, then adding sodium bicarbonate powder to disperse, cooling and centrifuging; adding the resultant to an aqueous solution of cyclodextrin, then adding an aqueous solution of sodium carboxymethyl cellulose, an acid and an initiator, heating for reaction, and drying to obtain a slightly cross-linked sodium carboxymethyl cellulose xerogel;
[0009] S3. Preparation of konjac composite xerogel: mixing slightly cross-linked konjac xerogel and slightly cross-linked sodium carboxymethyl cellulose xerogel to obtain konjac composite xerogel.
[0010] The mixture of slightly cross-linked sodium carboxymethyl cellulose and slightly cross-linked konjac glucomannan can produce obvious synergistic effects. The slightly cross-linked sodium carboxymethyl cellulose and konjac glucomannan contain a large number of hydroxyl and carboxyl groups in the two polymer chains, which are easy to produce hydrogen bond interactions, and can effectively achieve high swelling rate and rapid swelling of the product. In addition, the cross-linked carboxymethyl cellulose can adhere to the konjac into large blocks after absorbing water, and can also effectively provide a sense of fullness and prolong the fullness time. However, it will not be difficult to discharge due to excessive swelling, causing abdominal distension and affecting health. It can be eaten for a long time and has high adaptability among people.
[0011] The present invention improves the water absorption after cross-linking by introducing cyclodextrin in the polymer chain of sodium carboxymethylcellulose, and also introduces sodium bicarbonate powder to form porous structure, improves swelling rate.Sodium bicarbonate powder adopts glyceryl monostearate to coat, and glyceryl monostearate contains both hydrophilic structure and hydrophobic structure, and its hydrophobic long carbon chain can form inclusion action in the hydrophobic inner cavity of cyclodextrin, and then utilizes the cross-linking of cyclodextrin and sodium carboxymethylcellulose to improve dispersibility, and then optimizes the homogeneity of porous formation, and can further utilize cyclodextrin to improve water absorption.And, this porous structure is also conducive to the entanglement cross-linking between konjac xerogel molecules, and the mutual hydrogen bond interaction is better tight, and helps to form block by adhesion, improves satiety.
[0012] Preferably, in S2, the mass ratio of the glyceryl monostearate to the sodium bicarbonate powder is 3-5:1; and the particle size of the sodium bicarbonate powder is not greater than 10 μm.
[0013] The particle size of sodium bicarbonate affects its distribution in the gel, which in turn affects the formed porous structure.
[0014] Preferably, in S2, the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, the acid and the initiator is 3-5:100:100:0.1-0.2:0.1-0.2.
[0015] This mass ratio will affect the cross-linking effect between the molecular chains, and rapid swelling equilibrium and high water absorption can be achieved at this mass ratio.
[0016] Preferably, in S2, the mass concentration of the cyclodextrin aqueous solution is 2-3%; the mass concentration of the sodium carboxymethyl cellulose aqueous solution is 1-3%; and the acid is one or more of D-malic acid, L-malic acid, DL-malic acid, citric acid, fumaric acid, and tartaric acid.
[0017] Preferably, in S2, the viscosity of the aqueous solution of sodium carboxymethyl cellulose is 300 to 3000 mPa·s.
[0018] Preferably, in S2, the heating reaction is carried out by heating and stirring at a temperature of 35 to 45° C. for 3 to 4 hours.
[0019] Preferably, in S2, the drying is as follows: pouring the mixed solution obtained after the reaction into a mold with a solution thickness of 1 to 1.5 cm, pre-dehydrating and drying in a ventilated environment at 30 to 50° C. for 16 to 24 hours, and then vacuum drying at 90 to 120° C. for 10 to 12 hours with a vacuum degree of -0.04 to -0.08 MPa. After drying, cooling, demolding, and crushing are performed to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0020] Preferably, in S3, the mixing is such that the mass of the slightly cross-linked konjac xerogel accounts for 10 to 90% of the total mass.
[0021] Preferably, among S1, the preparation of described slightly cross-linked konjac xerogel is: konjac flour is added to 80~100 ℃ water, stirred for 2~4h, obtains the konjac aqueous solution that mass concentration is 1~3%, then adds 0~10% alkali of the konjac flour quality and stirs, then pours the solution into the mould while hot, the solution thickness is 1~1.5cm, dehydrates and dries in 30~50 ℃ of ventilated environment, and after drying, passes through demoulding, pulverizes, obtains slightly cross-linked konjac xerogel.
[0022] Preferably, in S1, the slightly cross-linked konjac xerogel is prepared by: adding konjac flour to water until it is completely dissolved to obtain a konjac aqueous solution; adding sodium polymethacrylate to ethanol, then adding sodium bicarbonate powder for dispersion, and then centrifuging to obtain a precipitate; adding the konjac aqueous solution and an initiator to a sodium hydroxide solution, then adding the precipitate for a first heating reaction, and filtering to obtain polymer I; adding polymer I to an acid solution, then adding amino acids and ultrasonicating, and filtering to obtain polymer II; adding polymer II to a sodium chloride solution, then heating for a second reaction, and post-processing to obtain a slightly cross-linked konjac xerogel.
[0023] Utilize alkali to deacetylate and crosslink konjac glucomannan in the prior art, but easily cause excessive crosslinking, make konjac glucomannan water absorption obviously decline, and the present invention is by adding NaHCO , it can produce bubble in acid solution and then give the porous structure that gel is abundant, this porous structure not only helps to fill and add amino acid small molecule, improve konjac gel texture, biocompatibility, and improve product added value, and help to be further composited with sodium carboxymethylcellulose macromolecular colloid, macromolecule can be better entangled mutually, improve structural stability, be conducive to forming the gel block with stable shape, promote satiety.Directly add NaHCO in konjac gel easily maldisperse, also easily just produce bubble in aqueous solution and form maldistributed porous structure, and at NaHCO Surface utilizes sodium polymethacrylate to carry out modification coating, can delay bubble generation, can also improve uniform distribution, can finally reach fast swelling balance by controlling gel crosslinking structure, and possess high water absorption.
[0024] Preferably, the viscosity of the konjac flour is 10000-35000 mPa·s, the mass concentration of the konjac aqueous solution is 1-3%, and the mass ratio of the sodium polymethacrylate to NaHCO3 is 5-10:1.
[0025] The mass ratio of sodium polymethacrylate and NaHCO3 affects the coating modification effect. If the mass ratio is too large, NaHCO3 will not be easy to foam to form a porous structure. If the mass ratio is too small, NaHCO3 will foam prematurely, which will affect the subsequent cross-linking effect.
[0026] Preferably, the mass ratio of the konjac aqueous solution, the initiator, the sodium hydroxide solution and the precipitate is 5000:3-5:1000:40-50. The first heating reaction is carried out at 55-60°C for 30-45 minutes.
[0027] Preferably, the mass ratio of the polymer I to the amino acid is 100:10-15; and the mass concentration of the sodium chloride solution is 20-25%.
[0028] The sodium chloride solution helps prevent excessive cross-linking of the konjac.
[0029] Preferably, the second heating reaction is carried out at 100-105° C. for 10-20 min.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The slightly cross-linked sodium carboxymethyl cellulose and konjac glucomannan contain a large amount of hydroxyl and carboxyl groups in the polymer chains, which are easy to produce hydrogen bond interactions, and can effectively achieve high swelling rate and rapid swelling of the product. In addition, the cross-linked carboxymethyl cellulose can adhere to konjac into large blocks after absorbing water, and can also effectively provide a sense of fullness and prolong the satiety time;
[0032] (2) By introducing cyclodextrin into the polymer chain of sodium carboxymethyl cellulose, the water absorption rate after cross-linking is improved. The introduction of sodium bicarbonate powder can form a porous structure, increase the swelling rate, and is also beneficial to the entanglement and cross-linking between konjac dry gel molecules. The hydrogen bond interaction between them is tighter, which helps to adhere to form blocks and improve satiety. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] Overall embodiment
[0035] A method for preparing a fast-swelling konjac composite xerogel comprises the following steps:
[0036] S1, the preparation of slightly cross-linked konjac xerogel: konjac flour is joined to 80~100 ℃ water, stir 2~4h, obtain mass concentration and be 1~3% konjac aqueous solution, then add 0~10% alkali of konjac flour quality and stir, then pour solution into mould while hot, solution thickness is 1~1.5cm, dehydrate in 30~50 ℃ of ventilated environment, after drying, through demoulding, pulverizing, obtain slightly cross-linked konjac xerogel;
[0037] Alternatively, the preparation of slightly cross-linked konjac xerogel: adding konjac flour with a viscosity of 10000 to 35000 mPa·s to water, heating to 80 to 100°C and stirring for 2 to 4 hours to completely dissolve the konjac, to obtain a konjac solution with a mass concentration of 1 to 3%; adding sodium polymethacrylate to ethanol, and then dispersing NaHCO3 therein, wherein the mass ratio of the sodium polymethacrylate to NaHCO3 is 5 to 10:1, and then centrifuging to obtain a precipitate; adding the konjac solution and an initiator (potassium persulfate or ammonium persulfate) to a sodium hydroxide solution, and then adding the precipitate to react at 55 to 60°C for 30 to 45 minutes, wherein the konjac solution and the initiator are , the mass ratio of sodium hydroxide solution and precipitate is 5000:3-5:1000:40-50, and after filtering, polymer I is obtained; polymer I is added to acid solution, and then amino acid is added and ultrasonicated, the mass ratio of polymer I and amino acid is 100:10-15, and after filtering, polymer II is obtained; polymer II is added to sodium chloride solution with a mass concentration of 20-25%, and reacted at 100-105°C for 10-20 minutes; the solution after reaction is poured into a mold while hot, the solution thickness is 1-1.5 cm, and it is dehydrated and dried in a ventilated environment at 30-50°C, and then demolded and crushed to obtain slightly cross-linked konjac dry gel.
[0038] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to ethanol and heat it, then add sodium bicarbonate powder (particle size not greater than 10 μm) for dispersion, the mass ratio of glyceryl monostearate to sodium bicarbonate powder being 3 to 5:1, cool and centrifuge; add the resultant to an aqueous solution of cyclodextrin with a mass concentration of 2 to 3%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 1 to 3% (viscosity of 300 to 3000 mPa·s), an acid and an initiator, the mass ratio of the resultant, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, the acid and the initiator being 3 to 5. : 100: 100: 0.1-0.2: 0.1-0.2, heating and stirring at a temperature of 35-45° C. for 3-4 hours, wherein the acid is one or more of D-malic acid, L-malic acid, DL-malic acid, citric acid, fumaric acid, and tartaric acid; pouring the mixed solution obtained after the reaction into a mold with a solution thickness of 1-1.5 cm, pre-dehydrating and drying in a ventilated environment at 30-50° C. for 16-24 hours, and then vacuum drying at 90-120° C. for 10-12 hours with a vacuum degree of -0.04--0.08 MPa, and cooling, demolding, and crushing after drying to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0039] S3. Preparation of konjac composite xerogel: mixing slightly cross-linked konjac xerogel and slightly cross-linked sodium carboxymethylcellulose xerogel, wherein the weight of slightly cross-linked konjac xerogel accounts for 10-90% of the total weight after mixing, to obtain konjac composite xerogel.
[0040] Example 1
[0041] A method for preparing a fast-swelling konjac composite xerogel comprises the following steps:
[0042] S1, the preparation of slightly cross-linked konjac xerogel: konjac flour (viscosity is 20000mPas) is joined in 95 ℃ water, stirred for 4h, obtaining mass concentration is 2% konjac aqueous solution, then add 5% sodium bicarbonate of konjac flour quality and stir, then pour solution into mould while hot, solution thickness is 1.5cm, dehydrate in 40 ℃ of ventilated environment, after drying, through demoulding, pulverizing, obtain slightly cross-linked konjac xerogel;
[0043] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to ethanol and heat to 60°C, stir until the solution is uniform, then add sodium bicarbonate powder (average particle size is 8 μm), stir and disperse for 30 minutes, wherein the mass ratio of glyceryl monostearate, sodium bicarbonate powder and ethanol is 4:1:20, cool and centrifuge; add the resultant to an aqueous solution of cyclodextrin with a mass concentration of 2.2%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 2% (viscosity is 2500 mPa·s), DL-apple Acid and potassium persulfate, wherein the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 3:100:100:0.15:0.1, and heating and stirring at a temperature of 40°C for 3 hours; pouring the mixed solution obtained after the reaction into a mold with a solution thickness of 1.5 cm, pre-dehydrating and drying in a ventilated environment at 45°C for 18 hours, and then vacuum drying at 110°C for 12 hours with a vacuum degree of -0.06MPa, cooling, demolding and crushing after drying to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0044] S3. Preparation of konjac composite xerogel: mixing slightly cross-linked konjac xerogel and slightly cross-linked sodium carboxymethylcellulose xerogel, wherein the mass of slightly cross-linked konjac xerogel accounts for 50% of the total mass after mixing, to obtain konjac composite xerogel.
[0045] Example 2
[0046] A method for preparing a fast-swelling konjac composite xerogel comprises the following steps:
[0047] S1. Preparation of slightly cross-linked konjac xerogel: adding konjac flour with a viscosity of 20000 mPa·s into water, heating to 95°C and stirring for 4 hours to completely dissolve the konjac, to obtain a konjac solution with a mass concentration of 2%; adding sodium polymethacrylate into ethanol, and then dispersing NaHCO3 therein, wherein the mass ratio of sodium polymethacrylate, NaHCO3 and ethanol is 8:1:50, and then centrifuging to obtain a precipitate; adding the konjac solution and potassium persulfate into a sodium hydroxide solution (pH value is 11.5-12), and then adding the precipitate to react at 60°C for 30 minutes, wherein the konjac solution, potassium persulfate, and hydroxyl radical are mixed into the precipitate. The mass ratio of sodium chloride solution to precipitate is 5000:4:1000:45, and after filtering, polymer I is obtained; polymer I is added to an aqueous solution of citric acid (pH value is 5-5.5), and then threonine is added and ultrasonicated, wherein the mass ratio of polymer I to amino acid is 100:15, and after filtering, polymer II is obtained; polymer II is added to a sodium chloride solution with a mass concentration of 25%, and reacted at 102°C for 15 minutes; the solution after the reaction is poured into a mold while hot, the solution thickness is 1.5 cm, and it is dehydrated and dried in a ventilated environment at 40°C, and then demolded and crushed to obtain a slightly cross-linked konjac dry gel.
[0048] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to ethanol and heat to 60°C, stir until the solution is uniform, then add sodium bicarbonate powder (average particle size is 8 μm), stir and disperse for 30 minutes, wherein the mass ratio of glyceryl monostearate, sodium bicarbonate powder and ethanol is 4:1:20, cool and centrifuge; add the resultant to an aqueous solution of cyclodextrin with a mass concentration of 2.2%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 2% (viscosity is 2500 mPa·s), DL-apple Acid and potassium persulfate, wherein the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 3:100:100:0.15:0.1, and heating and stirring at a temperature of 40°C for 3 hours; pouring the mixed solution obtained after the reaction into a mold with a solution thickness of 1.5 cm, pre-dehydrating and drying in a ventilated environment at 45°C for 18 hours, and then vacuum drying at 110°C for 12 hours with a vacuum degree of -0.06MPa, cooling, demolding and crushing after drying to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0049] S3. Preparation of konjac composite xerogel: mixing slightly cross-linked konjac xerogel and slightly cross-linked sodium carboxymethylcellulose xerogel, wherein the mass of slightly cross-linked konjac xerogel accounts for 50% of the total mass after mixing, to obtain konjac composite xerogel.
[0050] Example 3
[0051] A method for preparing a fast-swelling konjac composite xerogel comprises the following steps:
[0052] S1. Preparation of slightly cross-linked konjac xerogel: adding konjac flour with a viscosity of 20000 mPa·s into water, heating to 95°C and stirring for 4 hours to completely dissolve the konjac, to obtain a konjac solution with a mass concentration of 2%; adding sodium polymethacrylate into ethanol, and then dispersing NaHCO3 therein, wherein the mass ratio of sodium polymethacrylate, NaHCO3 and ethanol is 8:1:50, and then centrifuging to obtain a precipitate; adding the konjac solution and potassium persulfate into a sodium hydroxide solution (pH value is 11.5-12), and then adding the precipitate to react at 60°C for 30 minutes, wherein the konjac solution, potassium persulfate, and hydroxyl radical are mixed into the precipitate. The mass ratio of sodium chloride solution to precipitate is 5000:4:1000:45, and after filtering, polymer I is obtained; polymer I is added to an aqueous solution of citric acid (pH value is 5-5.5), and then threonine is added and ultrasonicated, wherein the mass ratio of polymer I to amino acid is 100:15, and after filtering, polymer II is obtained; polymer II is added to a sodium chloride solution with a mass concentration of 25%, and reacted at 102°C for 15 minutes; the solution after the reaction is poured into a mold while hot, the solution thickness is 1.5 cm, and it is dehydrated and dried in a ventilated environment at 40°C, and then demolded and crushed to obtain a slightly cross-linked konjac dry gel.
[0053] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to ethanol and heat to 60°C, stir until the solution is uniform, then add sodium bicarbonate powder (average particle size is 8 μm), stir and disperse for 40 minutes, wherein the mass ratio of glyceryl monostearate, sodium bicarbonate powder and ethanol is 5:1:20, cool and centrifuge; add the resultant to an aqueous solution of cyclodextrin with a mass concentration of 2.8%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 2% (viscosity is 2000 mPa·s), DL- Fruit acid and potassium persulfate, wherein the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 3:100:100:0.2:0.2, and heating and stirring at a temperature of 45°C for 4 hours; pouring the mixed solution obtained after the reaction into a mold, the solution thickness is 1.5 cm, pre-dehydrated and dried in a ventilated environment at 45°C for 22 hours, and then vacuum dried at 110°C for 10 hours, the vacuum degree is -0.06MPa, and after drying, it is cooled, demolded, and crushed to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0054] S3. Preparation of konjac composite xerogel: mixing slightly cross-linked konjac xerogel and slightly cross-linked sodium carboxymethylcellulose xerogel, wherein the mass of slightly cross-linked konjac xerogel accounts for 50% of the total mass after mixing, to obtain konjac composite xerogel.
[0055] Example 4
[0056] A method for preparing a fast-swelling konjac composite xerogel comprises the following steps:
[0057] S1. Preparation of slightly cross-linked konjac xerogel: adding konjac flour with a viscosity of 20000 mPa·s into water, heating to 95°C and stirring for 4 hours to completely dissolve the konjac, to obtain a konjac solution with a mass concentration of 2%; adding sodium polymethacrylate into ethanol, and then dispersing NaHCO3 therein, wherein the mass ratio of sodium polymethacrylate, NaHCO3 and ethanol is 8:1:50, and then centrifuging to obtain a precipitate; adding the konjac solution and potassium persulfate into a sodium hydroxide solution (pH value is 11.5-12), and then adding the precipitate to react at 60°C for 30 minutes, wherein the konjac solution, potassium persulfate, and hydroxyl radical are mixed into the precipitate. The mass ratio of sodium chloride solution to precipitate is 5000:4:1000:45, and after filtering, polymer I is obtained; polymer I is added to an aqueous solution of citric acid (pH value is 5-5.5), and then threonine is added and ultrasonicated, wherein the mass ratio of polymer I to amino acid is 100:15, and after filtering, polymer II is obtained; polymer II is added to a sodium chloride solution with a mass concentration of 25%, and reacted at 102°C for 15 minutes; the solution after the reaction is poured into a mold while hot, the solution thickness is 1.5 cm, and it is dehydrated and dried in a ventilated environment at 40°C, and then demolded and crushed to obtain a slightly cross-linked konjac dry gel.
[0058] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to ethanol and heat to 60°C, stir until the solution is uniform, then add sodium bicarbonate powder (average particle size is 8 μm), stir and disperse for 30 minutes, wherein the mass ratio of glyceryl monostearate, sodium bicarbonate powder and ethanol is 3.5:1:20, cool and centrifuge; add the resultant to an aqueous solution of cyclodextrin with a mass concentration of 3%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 2% (viscosity is 1600 mPa·s), DL-apple Acid and potassium persulfate, the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 3:100:100:0.15:0.1, and heating and stirring at a temperature of 40°C for 3 hours; pouring the mixed solution obtained after the reaction into a mold, the solution thickness is 1.5 cm, pre-dehydrating and drying in a ventilated environment at 45°C for 20 hours, and then vacuum drying at 110°C for 12 hours, the vacuum degree is -0.06MPa, and after drying, cooling, demolding, and crushing are performed to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0059] S3. Preparation of konjac composite xerogel: mixing slightly cross-linked konjac xerogel and slightly cross-linked sodium carboxymethylcellulose xerogel, wherein the mass of slightly cross-linked konjac xerogel accounts for 50% of the total mass after mixing, to obtain konjac composite xerogel.
[0060] Comparative Example 1
[0061] The difference from Example 2 is that the preparation of slightly cross-linked sodium carboxymethyl cellulose xerogel is different.
[0062] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add sodium carboxymethyl cellulose powder at a mass fraction of 2% into water, heat and stir in 30 degree water for 3 hours to completely dissolve the powder, and obtain an aqueous solution of sodium carboxymethyl cellulose (viscosity is 2500mPa·s); then add DL-malic acid at a mass fraction of 3% of sodium carboxymethyl cellulose and stir evenly, then pour the solution into a mold with a thickness of 1.5cm, pre-dehydrate and dry in a ventilated environment at 45°C for 18h, then vacuum dry at 110°C for 12h with a vacuum degree of -0.06MPa, and after drying, cool, demold and crush to obtain slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0063] Comparative Example 2
[0064] The difference from Example 2 is that no sodium bicarbonate was added in the preparation of the slightly cross-linked sodium carboxymethyl cellulose xerogel.
[0065] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to an aqueous solution of cyclodextrin with a mass concentration of 2.2%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 2% (viscosity of 2500mPa·s), DL-malic acid and potassium persulfate, wherein the mass ratio of glyceryl monostearate, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 1.2:100:100:0.15:0.1, and heat and stir at 40°C for 3h; pour the mixed solution obtained after the reaction into a mold with a solution thickness of 1.5cm, pre-dehydrate and dry in a ventilated environment at 45°C for 18h, and then vacuum dry at 110°C for 12h with a vacuum degree of -0.06MPa. After drying, cool, demold and crush to obtain slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0066] Comparative Example 3
[0067] The difference from Example 2 is that in the preparation of slightly cross-linked sodium carboxymethyl cellulose xerogel, the particle size of sodium bicarbonate powder is too large and the added amount is too much.
[0068] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to ethanol and heat to 60°C, stir until the solution is uniform, then add sodium bicarbonate powder (average particle size is 40 μm), stir and disperse for 30 minutes, wherein the mass ratio of glyceryl monostearate, sodium bicarbonate powder and ethanol is 4:1:20, cool and centrifuge; add the resultant to an aqueous solution of cyclodextrin with a mass concentration of 2.2%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 2% (viscosity is 2500 mPa·s), DL- Fruit acid and potassium persulfate, wherein the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 6:100:100:0.15:0.1, and heating and stirring at a temperature of 40°C for 3 hours; pouring the mixed solution obtained after the reaction into a mold, the solution thickness is 1.5 cm, pre-dehydrated and dried in a ventilated environment at 45°C for 18 hours, and then vacuum dried at 110°C for 12 hours, the vacuum degree is -0.06MPa, and after drying, it is cooled, demolded, and crushed to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0069] Comparative Example 4
[0070] The difference from Example 2 is that in the preparation of slightly cross-linked sodium carboxymethyl cellulose xerogel, the amount of glyceryl monostearate added is too much.
[0071] S2. Preparation of slightly cross-linked sodium carboxymethyl cellulose dry gel: add glyceryl monostearate to ethanol and heat to 60°C, stir until the solution is uniform, then add sodium bicarbonate powder (average particle size is 8 μm), stir and disperse for 30 minutes, wherein the mass ratio of glyceryl monostearate, sodium bicarbonate powder and ethanol is 10:1:20, cool and centrifuge; add the resultant to an aqueous solution of cyclodextrin with a mass concentration of 2.2%, then add an aqueous solution of sodium carboxymethyl cellulose with a mass concentration of 2% (viscosity is 2500 mPa·s), DL-apple Acid and potassium persulfate, wherein the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 6.6:100:100:0.15:0.1, and heating and stirring at a temperature of 40°C for 3 hours; pouring the mixed solution obtained after the reaction into a mold with a solution thickness of 1.5 cm, pre-dehydrating and drying in a ventilated environment at 45°C for 18 hours, and then vacuum drying at 110°C for 12 hours with a vacuum degree of -0.06MPa, cooling, demolding and crushing after drying to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel.
[0072] Comparative Example 5
[0073] The difference from Example 2 is that in the preparation of slightly cross-linked konjac xerogel, no sodium polymethacrylate coated modified NaHCO3 was added.
[0074] S1, preparation of slightly cross-linked konjac xerogel: konjac flour with a viscosity of 20000 mPa·s was added to water, heated to 95° C. and stirred for 4 h to completely dissolve the konjac to obtain a konjac solution with a mass concentration of 2%; the konjac solution and potassium persulfate were added to a sodium hydroxide solution (pH value was 11.5-12), and the mixture was reacted at 60° C. for 30 min, wherein the mass ratio of the konjac solution, potassium persulfate and sodium hydroxide solution was 5000:4:1000, and after filtering, a polymer I was obtained; the polymer The polymer I is added to an aqueous solution of citric acid (pH value is 5-5.5), and then threonine is added and ultrasonicated, wherein the mass ratio of polymer I to amino acid is 100:15, and after filtering, polymer II is obtained; polymer II is added to a sodium chloride solution with a mass concentration of 25%, and reacted at 102° C. for 15 minutes; the solution after the reaction is poured into a mold while hot, the solution thickness is 1.5 cm, and the solution is dehydrated and dried in a ventilated environment at 40° C., and then demolded and crushed to obtain a slightly cross-linked konjac xerogel.
[0075] Performance Testing
[0076] The konjac composite xerogel powders in the embodiments and comparative examples were tested, and their swelling degrees were calculated. The specific results are shown in Table 1.
[0077] Swelling degree: Take 1g of konjac composite xerogel powder and add it to 100g of pure water, stir and disperse it thoroughly with a glass rod, and the powder becomes gel-like after swelling. Then let it stand for 15min and 3h at room temperature respectively. The gel is deposited at the bottom of the beaker, and the upper solution is carefully poured out and removed. The remaining gel is weighed and the mass is recorded. Swelling degree = (gel mass / powder mass-1)*100%.
[0078] Table 1
[0079] Experimental Group Swelling degree in 15 minutes (%) 3h swelling degree (%) Example 1 53.97±2.63 62.68±2.97 Example 2 59.42±4.79 67.93±5.01 Example 3 56.71±2.98 66.85±3.17 Example 4 58.13±4.53 67.21±4.79 Comparative Example 1 26.82±0.61 48.16±0.64 Comparative Example 2 36.17±0.65 50.95±0.53 Comparative Example 3 40.14±0.21 51.87±0.29 Comparative Example 4 45.52±0.15 57.69±0.14 Comparative Example 5 42.41±0.13 53.53±0.11
[0080] As shown in Table 1, the present invention contains a large amount of hydroxyl and carboxyl groups in the two macromolecular chains of sodium carboxymethyl cellulose and konjac glucomannan after slight cross-linking, produces hydrogen bond interaction, can effectively realize high swelling rate and rapid swelling of product, and in addition, cross-linked carboxymethyl cellulose can adhere to konjac into large blocks after absorbing water, can also effectively provide satiety and extend satiety time.Comparative Example 1 shows that slight cross-linked sodium carboxymethyl cellulose gel can realize rapid swelling, and can improve water absorption.Comparative Examples 2-3 show that sodium bicarbonate helps gel to form a more porous structure, and the pore size is maintained within a reasonable range to help cross-link each other, and can also improve swelling rate, but the powder particle size of sodium bicarbonate is too large to cause water absorption and swelling rate to reduce.Comparative Example 4 shows that the addition amount of glyceryl monostearate is too much to be unfavorable for sodium bicarbonate foaming to form porous, and can have an impact on swelling rate.Comparative Example 5 shows that NaHCO3 is not added to have an impact on the porous structure of konjac glucomannan gel, causing it to be excessively cross-linked, and water absorption rate decreases.
[0081] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a fast-swelling konjac composite xerogel, characterized in that: The steps include: S1, konjac flour is joined in 95 ℃ water, stir 4h, obtain mass concentration and be 2% konjac aqueous solution, then add 5% sodium bicarbonate of konjac flour quality and stir, then pour solution in mould while hot, solution thickness is 1~1.5cm, dehydrate in ventilated environment, after drying, through demoulding, pulverizing, obtain slightly cross-linked konjac xerogel; S2. Add glyceryl monostearate to ethanol and heat to 60°C. Stir until the solution is uniform, then add sodium bicarbonate powder with an average particle size of 8 μm, stir and disperse for 30 minutes, the mass ratio of glyceryl monostearate, sodium bicarbonate powder and ethanol is 4:1:20, cool and centrifuge; add the obtained product to an aqueous solution of cyclodextrin with a mass concentration of 2.2%, and then add an aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate with a mass concentration of 2%, the mass ratio of the obtained product, the aqueous solution of cyclodextrin, the aqueous solution of sodium carboxymethyl cellulose, DL-malic acid and potassium persulfate is 3:100:100:0.15:0.1, heat and stir at 40°C for 3 hours; pour the mixed solution obtained after the reaction into a mold, the solution thickness is 1-1.5 cm, pre-dehydrate and dry in a ventilated environment, and then vacuum dry, cool, demold and crush after drying to obtain a slightly cross-linked sodium carboxymethyl cellulose dry gel; S3, mixing the slightly cross-linked konjac xerogel and the slightly cross-linked sodium carboxymethyl cellulose xerogel, wherein the weight of the slightly cross-linked konjac xerogel accounts for 50% of the total weight, to obtain a konjac composite xerogel.
2. the preparation method with fast swelling konjac composite xerogel as claimed in claim 1, is characterized in that, In S1, the viscosity of konjac flour is 20000 mPa·s.
3. the preparation method with fast swelling konjac composite xerogel as claimed in claim 1, is characterized in that, In S1, the solution thickness is 1.5 cm.
4. the preparation method with fast swelling konjac composite xerogel as claimed in claim 1, is characterized in that, In S1, dehydrate and dry in a ventilated environment at 30~50℃.
5. the preparation method with fast swelling konjac composite xerogel as claimed in claim 1, is characterized in that, In S2, the viscosity of the aqueous solution of sodium carboxymethyl cellulose is 300 to 3000 mPa·s.
6. the preparation method with fast swelling konjac composite xerogel as claimed in claim 5, is characterized in that, In S2, the viscosity of the aqueous solution of sodium carboxymethyl cellulose is 2500 mPa·s.
7. The method for preparing a fast-swelling konjac composite xerogel as claimed in claim 1, wherein: In S2, the solution thickness is 1.5 cm.
8. the preparation method with fast swelling konjac composite xerogel as claimed in claim 1, is characterized in that, In S2, pre-dehydrate and dry in a ventilated environment at 30~50℃ for 16~24h.
9. the preparation method with fast swelling konjac composite xerogel as claimed in claim 1, is characterized in that, In S2, it is then vacuum dried at 90 ~ 120 ° C for 10 ~ 12 hours, and the vacuum degree is -0.04 ~ -0.08MPa.
Citation Information
Patent Citations
Preparation method of cyclodextrin modified carboxymethyl cellulose hydrogel
CN111087625A
Pulverization of 'Konjak' powder and production of 'Konjak' or 'Konjak'-containing food using the fine 'Konjak' powder
JP1997000176A
Cited By
Preparation process and product of intragastric volume hydrogel
CN120173265A